Law of 'Isolation' and its legitimacy of practice in Sri Lanka: a Judicial Review - C. A Hettiarachchi; C. D. Attanayake; S. S. Wijesinghe (College of Community Physicians of Sri Lanka, 2022)
Introduction: Isolation of persons is a key strategy to prevent and control highly contagious diseases throughout the history worldwide and its importance had re-emerged due to COVID-19 pandemic. In Sri Lanka, like other countries, this isolation process is mainly governed by the law. The Quarantine and Prevention of Diseases Ordinance is the main law in this regard where the powers are mainly vested with health authorities. Objectives: To analyses the law of isolation and its legitimacy of practice in Sri Lanka Methods: A desk review of laws associated with isolation and quarantine in Sri Lanka was conducted and compared with the actual practice of implementation of these laws during COVID-19 epidemic. Results: Quarantine and Prevention of Diseases Ordinance of Sri Lanka and its regulations contain strong provisions on isolation of persons which are incorporated in to legal scenarios of disease locality, infected house/place, self-quarantine and observational hospital/place and linked to face mask and social distancing rules. However, these legal provisions are misused and not legitimately implemented by authorities. Conclusions and Recommendations: Quarantine and Prevention of Diseases Ordinance of Sri Lanka and its regulations can be used to prevent and control COVID-19 effectively as adequate and powerful provisions are available, especially in relevant to isolation of persons. However, the relevant law is often wrongly interpreted and imposed by authorities as well as non-authorities. Authorities and Authorized Officers need to be empowered on their powers and limitations to implement the law legitimately in order to achieve the maximum control and prevention of COVID-19 and other infectious diseases.